Workplace health promotion programs in different areas of Europe (Epidemiology, Biostatistics, and Public Health, 2022)
BackgroundAging of the workforce challenges European countries. Keeping aged workers healthy and productive, through health promotion, is a key goal of European labour policy. The aim of the present study was to collect experiences of workplace health promotion for older workers (WHPOW) conducted in 10 representative countries of Central Europe, Eastern Europe and the Mediterranean.MethodsA literature review of activities of WHPOW was conducted through a comprehensive search of major scientific databases and on the website of the major European Agencies on worker health promotion. The search was restricted to papers published in English from 2000 to 2015. Companies were asked for additional documentation about WHPOW programmes in a survey conducted with SurveyMonkey.ResultsA total of 756 initiatives regarding WHPOW were identified. 134 of these were guidelines, regulations, or review studies. The remaining 622 activities were intervention studies performed or promoted in the workplace and targeted at older workers or at the aging of the workforce. Most of the programs were carried out in Central Europe (295, 47.4%), less in East Europe (193, 31.0%) and in Mediterranean countries (134, 21.6%).ConclusionOur study shows that there are only a limited number of WHPOW actions throughout the 10 selected European Countries. While in Central Europe widespread interest in issues of aging workforce has resulted in national policies to encourage WHPO, not all the countries of Eastern Europe are equally well equipped. Lastly, in Southern Europe health promotion activities are largely inadequate compared to needs.